2012
DOI: 10.1186/1471-2172-13-33
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus anthracis’ lethal toxin induces broad transcriptional responses in human peripheral monocytes

Abstract: BackgroundAnthrax lethal toxin (LT), produced by the Gram-positive bacterium Bacillus anthracis, is a highly effective zinc dependent metalloprotease that cleaves the N-terminus of mitogen-activated protein kinase kinases (MAPKK or MEKs) and is known to play a role in impairing the host immune system during an inhalation anthrax infection. Here, we present the transcriptional responses of LT treated human monocytes in order to further elucidate the mechanisms of LT inhibition on the host immune system.ResultsW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…NSF gene has been associated with Parkinson’s disease [39]. In one study ARL17 , ADP-ribosylation factor-like 17 was one of the genes reported to be differentially regulated in the human monocytes after treatment with anthrax lethal toxin (LT) [40]. ARL17 is localized to the Golgi apparatus and is thought to be involved in modulation of vesicle budding and is known to be an activator of cholera toxin catalytic subunit, an ADP-ribosyltransferase [41].…”
Section: Discussionmentioning
confidence: 99%
“…NSF gene has been associated with Parkinson’s disease [39]. In one study ARL17 , ADP-ribosylation factor-like 17 was one of the genes reported to be differentially regulated in the human monocytes after treatment with anthrax lethal toxin (LT) [40]. ARL17 is localized to the Golgi apparatus and is thought to be involved in modulation of vesicle budding and is known to be an activator of cholera toxin catalytic subunit, an ADP-ribosyltransferase [41].…”
Section: Discussionmentioning
confidence: 99%
“…For each dataset, we used the differentially expressed genes published by authors (HAM-LT-ET by Dozmorov et al [79] and PBMC exposed to LT by Chauncey et al [80]) and reported in the GEO (Gene Expression Omnibus; ).…”
Section: Methodsmentioning
confidence: 99%
“…This information has largely been obtained from in vitro infection experiments. Primary cells taken from naïve human volunteers [8][9][10][11][12][13][14][15] or continuous cell lines [16][17][18][19][20][21][22] have been infected and incubated with a pathogen for different time periods (ranging from 1 to 48 hours) and host gene signatures generated ( Table 1). Microarray studies performed in this way provide insights into the cellular response following infection with, for instance, Monkeypox virus.…”
Section: Dna Microarraysmentioning
confidence: 99%
“…DNA microarray analysis has been used to improve our understanding of the host response following exposure to the bacterium [18], spores [9], edema toxin [17], and lethal toxin [8] of Bacillus anthracis, the causative agent of anthrax. Studies on human peripheral monocytes revealed that anthrax lethal toxin targets multiple normal immuneregulatory pathways that would be expected to protect the host against anthrax infection.…”
Section: Dna Microarraysmentioning
confidence: 99%
See 1 more Smart Citation